Fetal cardiomyopathy in neurofibromatosis type I: Novel phenotype and review of the literature. Issue 6 (28th March 2019) - Ritter, Alyssa; Cuddapah, Sanmati; Degenhardt, Karl; Kasperski, Stefanie; Johnson, Mark P.; O'Connor, Matthew J.; Ahrens‐Nicklas, Rebecca
Abstract : Neurofibromatosis type I (NF1) is a relatively common genetic disorder characterized by neurocutaneous lesions, neurofibromas, skeletal anomalies, iris hamartomas, and predisposition to other tumors. NF1 results from heterozygous loss‐of‐function mutations in neurofibromin ( NF1 ), and diagnosis is most often made using clinical diagnostic criteria. Cardiac manifestations of NF1 include congenital heart disease (such as valvar pulmonary stenosis), left ventricular hypertrophy, and adult‐onset pulmonary hypertension. Prenatal features of NF1 are often nonspecific and diagnoses are infrequently made prenatally without a known family history. Herein, we report the first case, to the best of our knowledge, of fetal cardiomyopathy as the presenting feature in NF1 and review NF1‐related left ventricular hypertrophy. NF1 should be considered in the differential diagnosis for fetuses with cardiomyopathy, even in the absence of a known family history of the condition.